Retrograde femoral nailing for deformity correction and fracture treatment in osteogenesis imperfecta: clinical and radiological assessment of a novel technique - Georges Samuel; Saliba Ibrahim; Finidori Georges; Haumont Edouard; Pannier Stephanie; Pejin Zagorka (SICOT-J)
Introduction: Intramedullary anterograde femoral nailing is a standard treatment for femoral deformity and fracture in osteogenesis imperfecta (OI). This study evaluates the clinical and radiological outcomes of a novel retrograde femoral nailing technique. Methods: A retrospective analysis was performed on 31 patients with OI who underwent retrograde femoral nailing using Dubow–Bailey nails from 2004 to 2019. A total of 54 femurs were treated for femoral deformity or fracture by three senior surgeons, with a mean follow-up of 2.7 years. Clinical outcomes, including knee range of motion and pain, were assessed. Radiological outcomes included deformity angle (DA), neck shaft angle (NSA), mechanical lateral distal femoral angle (mLDFA), and nail positioning on AP and lateral X-rays. Potential complications, including hip osteonecrosis, distal femoral growth arrest, and infections, were also evaluated. Results: The procedure showed favorable outcomes, with no postoperative knee motion limitations or persistent pain. The mean pre-operative DA on AP and lateral views was 29° and 40°, respectively, with no residual deformity after surgery. The mean NSA and mLDFA were 132° and 101° before surgery, compared to 143° and 89° post-operatively. Nail alignment was optimal in 81% of the femurs, with proper positioning in both the distal epiphysis and femoral neck. No cases of hip osteonecrosis, distal femoral growth arrest, or infection were reported. Hardware migration occurred in seven cases. Conclusion: Retrograde femoral nailing is a safe and effective technique for managing femoral deformities and fractures in OI.